2023
DOI: 10.3389/fphys.2023.1210449
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in the relationship between periodontitis and systemic diseases

Abstract: Periodontitis is a common inflammatory disease. It is characterized by destruction of the supporting structures of the teeth and could lead to tooth loss and systemic inflammation. Bacteria in inflamed gingival tissue and virulence factors are capable of entering the bloodstream to induce systemic inflammatory response, thus influencing the pathological process of many diseases, such as cardiovascular diseases, diabetes, chronic kidney disease, as well as liver injury. An increasing body of evidence show the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…More recently, Yoshino et al [27], using Electron Spin Resonance, demonstrated that evaluation of the salivary antioxidant activity towards O.2 might be an effective parameter for the objective assessment of PD progression. Therefore, an imbalance between oxidative stress and antioxidant capacity played a crucial role in the pathogenesis of PD [28,29], but it still needed to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Yoshino et al [27], using Electron Spin Resonance, demonstrated that evaluation of the salivary antioxidant activity towards O.2 might be an effective parameter for the objective assessment of PD progression. Therefore, an imbalance between oxidative stress and antioxidant capacity played a crucial role in the pathogenesis of PD [28,29], but it still needed to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…(5) The host immune response causes most periodontal tissue damage, involving leukocytes, complement, and reactive oxygen species (ROS). (10,11) Once the level of damage surpasses the cell's ability to repair, it will induce permanent cell cycle arrest and changes in secretory phenotype reminiscent of the aging response. (12) Free radicals can lead to oxidative stress by causing an imbalance between oxidants and antioxidants, possibly damaging cells.…”
Section: Introductionmentioning
confidence: 99%